Toward a Redefinition of “Educational” in Babies’ and Toddlers’ Media:Overt Visual Attention, Verbalization, and Other Measures of Engagement as Indicators of Learning - Ryan, Erin Leigh (Advances in Social Sciences Research Journal, 2014)
This paper provides an analysis of data from an earlier study in which children 12- to 24-months failed to learn from an educational infant DVD. Whereas children performed no better than chance on the original posttests, coders noticed verbal and nonverbal behaviors that appeared to indicate engagement with the content while it was playing. After an analysis of the videotaped trials, this project uncovered several behaviors indicating engagement, such as unprompted verbalizations of items on screen, verbal imitations of items on screen, non-verbal indications of engagement with the program, program elicited amusement, and both verbal and nonverbal behavior directed at the DVD player itself. Results are discussed in the context of Sproull (1973) and Crawley et al.’s (2002) findings that direct reactions to program content are indicators of “vicarious participation” which is a reflection, rather than a cause, of learning.